Current understanding on the role of CCT3 in cancer research - Liu, Wenlou; Lu, Yu; Yan, Xiang; Lu, Quansheng; Sun, Yujin; Wan, Xiao; Li, Yizhi; Zhao, Jiaqin; Li, Yuchen; Jiang, Guan (Frontiers in Oncology, 2022)
Chaperonin containing TCP1 Subunit 3 (CCT3) is an important member of the chaperone protein family, providing a favorable environment for the correct folding of proteins in cell division, proliferation, and apoptosis pathways, which is involved in a variety of biological processes as well as the development and invasion of many malignant tumors. Many malignancies have been extensively examined with CCT3. It is presently used as a possible target for the treatment of many malignancies since it is not only a novel biomarker for the screening and diagnosis of different tumors, but it is also closely associated with tumor progression, prognosis, and survival. Recent studies have shown that the expression of CCT3 is up-regulated in some tumors, such as liver cancer, breast cancer, colon cancer, acute myeloid leukemia, etc. In this paper, we review the role of CCT3 in various tumors.